2022
DOI: 10.3389/fmed.2022.789414
|View full text |Cite
|
Sign up to set email alerts
|

Gout Arthritis During Admission for Decompensated Heart Failure—A Descriptive Analysis of Risk Factors, Treatment and Prognosis

Abstract: BackgroundChronic heart failure and hospital admissions are well-known risk factors for acute gouty arthritis. However, in-depth analyses of patients admitted for decompensated heart failure (DHF) who subsequently developed a gout attack are sparse. This study aims to characterize DHF patients who developed a gout attack during their inpatient treatment and describe potential risk factors, its consequences, and its management in the setting of heart failure exacerbation.MethodsRetrospective chart review of 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
2
0
0
2
Order By: Relevance
“…The median hospital and ICU LOS of Impella-supported patients with gout flares was 24 days and 25 days longer, respectively, compared to those without gout flares. These findings align with previous research that has consistently reported similar trends in various medical contexts [ 23 25 ]. These observations could be attributed to the need for additional diagnostic studies, inpatient consultations, and therapies, which may result in extended hospital stays.…”
Section: Discussionsupporting
confidence: 92%
“…The median hospital and ICU LOS of Impella-supported patients with gout flares was 24 days and 25 days longer, respectively, compared to those without gout flares. These findings align with previous research that has consistently reported similar trends in various medical contexts [ 23 25 ]. These observations could be attributed to the need for additional diagnostic studies, inpatient consultations, and therapies, which may result in extended hospital stays.…”
Section: Discussionsupporting
confidence: 92%
“…The median hospital and ICU LOS of Impella-supported patients with gout ares was 24 days and 25 days longer, respectively, compared to those without gout ares. These ndings align with previous research that has consistently reported similar trends in various medical contexts [20][21][22]. These observations could be attributed to the need for additional diagnostic studies, inpatient consultations, and therapies, which may result in extended hospital stays.…”
Section: Discussionsupporting
confidence: 90%
“…Другим потенциальным показанием для назначения анакинры при РА (и других ИВЗ) является развитие резистентного перикардита и плеврита [291]. Следует иметь в виду целесообразность применения анакинры у тяжелых пациентов с подагрическим артритом и другими микрокристаллическими артритами, частыми коморбидными патологиями при которых являются ЗСН, СД2 и хроническая болезнь почек [102, [292][293][294], затрудняющие применение стандартной терапии (НПВП, глюкокортикостероиды).…”
Section: Discussionunclassified
“…Научно-практическая ревматология. 2022;60(3):[280][281][282][283][284][285][286][287][288][289][290][291][292][293][294][295][296][297][298] …”
unclassified